Collective Climate: Agreement as a Basis for Defining Aggregate Climates in Organizations - Joyce, William F.; Slocum, John W. (Academy of Management Journal, 1984)
Agreement of psychological climate perceptions is proposed as a basis for a composition theory of aggregate climate. Climates based on agreement, termed ?collective climates,? are shown to meet several requirements for construct validity including internal consistency, discrimination, and predictable relationship to relevant criteria. Personal and setting characteristics related to membership in collective climates are determined.